3D-Printed Fast-Dissolving Oral Dosage Forms via Fused Deposition Modeling Based on Sugar Alcohol and Poly(Vinyl Alcohol)-Preparation, Drug Release Studies and In Vivo Oral Absorption - Sorato Ikeda; Masanori Kobayashi; Soken Aoki; Takayuki Terukina; Takanori Kanazawa; Hiroyuki Kojima; Hiromu Kondo (MDPI AG, 2023)
Three-dimensional printing technology holds marked promise for the pharmaceutical industry and is now under intense investigation. Most research is aimed at a greater efficiency in printing oral dosage forms using powder bed printing or fused deposition modeling (FDM). Oral dosage forms printed by FDM tend to be hard objects, which reduce the risk of cracking and chipping. However, one challenge in printing oral dosage forms via FDM is achieving rapid drug release, because the materials for FDM are basically thermoplastic polymers with slow drug release properties. In this study, we investigated printing a fast-dissolving oral dosage form by adding sugar alcohol to a poly(vinyl alcohol)-based formulation for FDM. Filaments which contain sugar alcohol were successfully prepared, and objects were printed with them as oral dosage forms by FDM. On drug release testing, a printed oral dosage form in a ring shape which contained 55% maltitol showed a more than 85% drug release in 15 min. In vivo oral absorption of this printed oral dosage form in dogs was comparable to that of a conventional fast-dissolving tablet. Of particular interest, the drug release profile and drug amount of the oral dosage forms can be easily controlled by a change in shape using 3D Computer Aided Design. These characteristics will encourage the prevalence of FDM by the pharmaceutical industry, and contribute to the promotion of personalized medicine.